3D MODELLING OF ANDESITE USING RESISTIVITY DATA IN KALISONGGO MOUNT, KULON PROGO - Trianda, Obrin; Prastowo, Rizqi (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2018)
The needs for andesite stone for development in Kulon Progo is increasing, so a new andesite reserve is needed. This study aims to map andesit distribution in 2-D or 3-D in the research area. The determination of andesite distribution is based on the difference between the andesite resistivity value and the surrounding rocks. Geologically, Mount Kalisonggo and Songgo River are included in the Old Andesite Formation with the appearance of the colummnar joint structure.Field data was collected using a Geolistrik method with dipole-dipole configuration of 5 paths. The resistivity data is processed and modeled 2D using Res2Dinv software, so that the andesite resistivity cross-section model is obtained. Andesite distribution after the 2-D or 3-D modeling obtained thickness varies between 5-17 meters.